The Role of Artificial Intelligence in Enhancing Global Internal Audit Efficiency: An Analysis - Ghafar, Iyad; Perwitasari, Widya; Kurnia, Rama (Universitas Diponegoro, 2024)
This research paper explores the transformative role of artificial intelligence (AI) in enhancing the efficiency and effectiveness of global internal audit functions. As businesses increasingly adopt AI-driven technologies, internal auditing has witnessed significant advancements in data analysis, risk detection, compliance monitoring, and decision-making processes. The paper analyzes how AI tools like machine learning, natural language processing, and predictive analytics contribute to the automation of repetitive audit tasks, the detection of anomalies, and the improvement of audit accuracy and timeliness. Additionally, it addresses the challenges associated with AI adoption, including data privacy concerns, skills gaps among auditors, and the integration of AI into existing audit frameworks. The study also provides a comparative analysis of AI-enabled versus traditional audit practices, highlighting AI’s potential to enhance audit quality, reduce operational costs, and provide deeper insights into financial and non-financial risks. By examining case studies and industry practices, the paper emphasizes AI’s critical role in shaping the future of internal auditing on a global scale. The findings suggest that AI’s integration into internal audits is not just a trend but a necessary evolution for achieving optimal audit outcomes.